ОСНОВНІ ПІДХОДИ ДО УТВОРЕННЯ ПРИЙОМІВ, МЕТОДІВ ТА МЕТОДИК НАВЧАННЯ ІСТОРІЇ, ЇХ УПОРЯДКУВАННЯ ТА СИСТЕМАТИЗАЦІЇ (Педагогіка вищої та середньої школи, 2006)
The article deals with the questions of forming of system of mode and methods in a historical education as a necessity that is naturally stipulated by the condition of reformation and closing to the European and world standards. Some aspects of practical realization of this task are revealed.